Experience in implementing a program for basic life support and available automated defibrillation in a cancer center - M. A. Cherkashin; A. A. Nikolaev; N. A. Berezina; N. S. Berezin; T. V. Bolshakova (Российский кардиологический журнал)
Unified approaches to ensuring the chain of survival can improve the patient’s prognosis both in out-of-hospital and in-hospital cardiac arrest.Aim. To discuss practical issues of introducing a program for the availability of automated external defibrillation in a cancer center.Material and methods. For four years, our healthcare facility has been implementing a training program for basic and advanced life support according to the European Resuscitation Council standards, combined with the creation and development of an infrastructure for the availability of automatic defibrillation. A roadmap and infrastructure were developed for the project implementation.Results. In 2018-2022, 229 employees (114 doctors, 85 nurses and 30 nonmedical workers) were trained under the basic life support program. Fifteen defibrillators were placed in various units. During the specified period, first aid in case of sudden cardiac arrest using an automated external defibrillator before the resuscitation team arrival was independently provided by doctors and nurses of departments three times. To implement training in the continuous education system, the curriculum has passed the examination and accreditation in the edu. rosminzdrav system.Conclusion. The development and implementation of such initiatives requires significant organizational and methodological work, including continuous education system. However, in our opinion, this is an extremely useful tool for improving the safety and quality of medical care.